(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Valore intrinseco della natura ed economia umana - 2. Caratteristiche e implicazioni delle teorie antropocentriche - 3. Sull’approccio antropocentrico dell’attuale declinazione giuridica della sostenibilità dell’agire scientifico nei confronti dell’ambiente e della vita, e sui suoi limiti - 4. Il principio dello sviluppo sostenibile - 5. Limitare lo sviluppo non significa impedirlo - 6. Sulla necessità di limiti per l’autonomia tecnocratica. On a harmonious relationship between man and nature: an ethical-juridical reflection ABSTRACT: The break in the harmonious relationship between man and nature has been evident for some decades now. This break is the consequence of the use of science and technology in the interest of only some, an approach that led to an exploitation of nature not respectful of its intrinsic value. Hence the technocracy. In fact, today we are witnessing the domination of the technocratic power, which has as its purpose the utility for those who manage it, in the absence of consideration of the damage that derives from the realization of profit. This latter position marries the anthropocentric conception in the relationship between man and nature and blows both the religious vision of this relationship, which entrusts man with power over nature, but also the duty to guard it, and the natural-evolutionary vision. Hence the need for a limitation of the autonomy of scientific action to effectively protect the ecosystem.